Management of intraocular pressure and inflammation using febuxostat film: in vitro - in vivo correlation - Mouli Das; Sk Habibullah; Tanisha Das; Rakesh Swain; Subrata Mallick (ADMET and DMPK)
Background and purpose: Urate crystal accumulation may lead to the condition of ocular tophaceous gout, causing ocular inflammation and increased intraocular pressure (IOP) due to the triggering of several inflammatory receptors like NLRP3, A2A, and TLR4. The study has been undertaken to manage intraocular pressure and inflammation using febuxostat (FBX) film formulation for sustained and improved activity, particularly for long-term tophaceous gout patients. Experimental approach: Hydroxypropyl methyl-cellulose K100 matrix-based hydrogel film of FBX has been fabricated in the presence of plasticizers like triethanolamine, dimethyl-sulphoxide (DMSO), or polyethylene glycol 600 using casting and evaporation technique. Carrageenan was injected into the upper palpebral region to induce ocular inflammation, and a normotensive rabbit eye model was used for monitoring IOP. Key results: Amorphization of the drug was observed from the differential scanning calorimetry and X-ray diffraction results. In vitro release study revealed an improved and diffusion-controlled sustained drug release for more than 5 h (62.69 to 84.76 %). Compared to its absence, decreased IOP was extended up to 5 h using film (with DMSO). Disappearance of ocular inflammation was also observed in the test animals after 2.5 h of film application, whereas acute inflammation was continued in the group without treatment for more than 4 h. Docking study revealed good binding interaction of drug and NLRP3, A2A, and TLR4 receptor. Conclusion: Febuxostat-loaded hydrogel-forming plasticized film could be utilized to better manage and control ocular inflammation and associated IOP, particularly in ocular tophaceous gout patients.